Evaluating the performance of employees in Algerian institutions - BOUBERTAKH, Abdelkrim (Journal of Human Sciences, 2025)
Through this study, we aim to identify the employee performance evaluation system applied in the Algerian institution, analyze this system, identify its strengths and weaknesses, understand its components, and how to benefit from its application in order to maximize its gains for the institution and employees.It was concluded through this study that institutions evaluate the performance of employees using a set of standards and methods in order to correct the course of the institution and achieve continuity and growth for it by adapting to internal and external conditions and developing the individual competencies and capabilities of its employees.